The EuropaBON Stakeholder Dashboard: A dynamic web application to map Europe’s biodiversity community - Christian Langer; Jessica Junker; Marek Giergiczny; Ian McCallum; Ivelina Georgieva; Henrique Miguel Pereira (PLoS ONE, 2025)
Europe’s biodiversity faces increasing pressure from climate change, pollution, and habitat loss, while governments struggle to sustain the monitoring efforts required to respond effectively to these challenges. Addressing this gap calls for a coordinated and inclusive approach that brings together all relevant biodiversity stakeholders to co-design a robust European biodiversity monitoring system. To support this, the Europa Biodiversity Observation Network (EuropaBON) has established one of the most comprehensive biodiversity stakeholder networks in Europe. To analyse this community and support evidence-based improvements, we developed the EuropaBON Stakeholder Dashboard – a dynamic, interactive web application that maps and visualises the EuropaBON stakeholder network’s structure in real-time. Accessible at https://europabon.org/dashboard, the dashboard enables users to explore stakeholder connections across three key dimensions: occupational sector, realm (terrestrial, freshwater, marine), and geographic region. It displays detailed network graphs, an interactive map, and summary statistics that highlight institutional positions in biodiversity data flows (e.g., data users, data providers, or both), levels of participation in EuropaBON activities, and connections to key EU projects and infrastructures. Users can identify the most central and active institutions in the network, filter and download data, and assess coverage across different thematic areas and regions. This tool supports both researchers and policymakers by offering an up-to-date overview of who is involved in biodiversity monitoring across Europe, where collaborations exist, and where further engagement is needed. By combining technological integration with stakeholder participation, the EuropaBON Stakeholder Dashboard enhances transparency, promotes inclusivity, and contributes to a more coordinated and effective biodiversity monitoring landscape in Europe.